Optimizing solar drying efficiency: Effects of PCM, and IR on energy and exergy performance. - Mehdi Moradi; Reza Raeesi; Dariush Zare; Mahdi Keramat-Jahromi (PLoS ONE)
This study investigates the drying behavior of potatoes using a hybrid solar dryer equipped with a Compound Parabolic Concentrator (CPC) collector, Phase Change Materials (PCM), and Infrared Radiation (IR). Drying experiments were conducted at 40°C, 50°C, and 60°C under different PCM and IR configurations to evaluate drying kinetics, energy consumption, and product color quality. Energy and exergy analyses, along with assessments of drying time and color change (ΔE), were performed to identify the most efficient drying conditions. This study introduces a novel integration of PCM and IR in a hybrid solar drying system, providing a unique approach to optimizing energy efficiency, and product quality. The results demonstrated that PCM significantly improved the drying process by reducing drying time by an average of 5.3%, stabilizing the thermal environment, and enhancing both energy and exergy efficiency. The lowest Specific Energy Consumption (SEC) and shortest drying time were recorded at 60°C with PCM and IR, demonstrating the efficiency of this setup in reducing energy consumption while ensuring high drying performance. IR alone reduced drying time by 40%, accelerating moisture removal considerably. However, while the combination of PCM and IR enhanced thermal stability, it slightly prolonged drying time due to PCM's heat absorption characteristics. Among the tested conditions, 60°C with PCM and IR was identified as the optimal setting, achieving the lowest SEC while minimizing drying time and color degradation. This study highlights the importance of integrating PCM and IR into solar drying systems to enhance efficiency, reduce energy consumption, and improve product quality. Future research should explore additional drying techniques, such as microwave and ultrasound-assisted drying, to further optimize hybrid solar drying systems.